2011
DOI: 10.1007/s11434-010-4307-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential hazards from teletsunami in China: Tidal observations of a teletsunami generated by the Chile 8.8 M w earthquake

Abstract: an earthquake of M w 8.8 rocked the central coast of Chile. A teletsunami was triggered by the huge earthquake and then propagated across the entire Pacific in less than 24 h. The initial tsunami wave arrived at the southeast coast of China at 16 : 20 on February 28 and was recorded in real time by a number of tidal gauges off mainland China and Taiwan Province. The teletsunami waves have never been recorded with such a broad geographical scope in China before this event. The aim of the present work is to repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
2
8
3
Order By: Relevance
“…Therefore, the exact sea-level anomaly induced by the Chilean tsunami is difficult to calculate. Yu et al [9] found that the sea-level anomaly induced by the Chilean tsunami near Xiaoqushan Island was around 0.1 m, which differs from the value of 0.48 m determined in this paper. The difference is understandable in that the different measurements were obtained at different locations with different topography and analyzed using different methods.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, the exact sea-level anomaly induced by the Chilean tsunami is difficult to calculate. Yu et al [9] found that the sea-level anomaly induced by the Chilean tsunami near Xiaoqushan Island was around 0.1 m, which differs from the value of 0.48 m determined in this paper. The difference is understandable in that the different measurements were obtained at different locations with different topography and analyzed using different methods.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that a tsunami with periods of 50-150 min contributed largely to the local sea-level anomaly around Xiaoqushan Island. This result is consistent with the result of Yu et al [9] that the Chilean tsunami propagating into the East China Sea had periods of 35-100 min. The large values in the spectrum at low frequencies are probably due to background signals, such as signals of surges or wind waves propagating from other seas, not being filtered out.…”
Section: Sea-level Anomaly Induced By the Chilean Earth-quake Tsunamisupporting
confidence: 93%
See 2 more Smart Citations
“…The real-time series of sea level data obtained from CTD at Xiaoqushan Seafloor Observatory is used to learn how tsunami in remote regions may impact the coastal processes off the ECS. The tsunami, for example, induced by the 2010 Chile earthquake occurred off the coast of the Maule Region of Chile at 14:43 on Feb. 27 in 2010 (Beijing time, the first green pentagram labeled in Figure 6b) rating a magnitude of 8.8 on the moment magnitude scale, affected most of the Pacific ocean region [12,13]. According to the seismic wave propagation, P-wave and S-wave arrived at Xiaoqushan Seafloor Observatory 20 and 27 h later, respectively.…”
Section: Sea Level Anomaly Induced By the Earthquake In Chilementioning
confidence: 99%